An analysis on sustainability reporting practices of the Turkish banking sector. (12th February 2020) - Menteş, S. Ahmet
Stakeholders increasingly expect firms to disclose their activities and the effects of these activities on environment and society. Banks and other financial institutions are no exception and face similar pressure from all stakeholders to be more transparent. This study uses global reporting initiative guidelines to explore the sustainability reporting practices of the Turkish banking sector. All of the 52 banks that operate in Turkey as of 2015 are included in the study. Results exhibit that only nine banks release sustainability reports. The economic (EC) dimension indicators of sustainability reports have the highest disclosure rate among reporting banks. On the other hand financial services sector (FS) supplement has the lowest disclosure rate among reporting banks compared to other dimensions of sustainability reporting. Findings also indicate that the asset size of sustainability report releasing banks add up to more than 75% of the banking sector in Turkey.